Method for enhancing performance of cement mortar through acidification electric field pre-carbonization

Through the pre-carbonization method of acidizing electric field, acetic acid treats the cement slurry and applies DC electric to CO2, which solves the problems of CO2 emissions and performance reduction in cement production, and achieves efficient CO2 absorption and improvement of cement mortar performance.

CN120349135AActive Publication Date: 2025-07-22DALIAN MARITIME UNIVERSITY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510539618.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-27
Publication Date
2025-07-22
Estimated Expiration
2045-04-27

AI Technical Summary

Technical Problem

Cement production emits a large amount of greenhouse gas CO2, which is slow in natural absorption and may lead to corrosion of steel bars and reduces the performance of cement mortar.

Method used

The pre-carbonization method of acidification electric field is used to treat the cement slurry through acetic acid and apply DC power, and CO2 is introduced at the same time to promote the dissolution of active substances and the formation of calcium carbonate, forming nano-scale calcium carbonate particles, and enhancing the performance of cement mortar.

Benefits of technology

Significantly improve the mechanical properties and CO2 absorption capacity of cement mortar, reduce production costs, and improve concrete strength and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120349135A_ABST
    Figure CN120349135A_ABST
Patent Text Reader

Abstract

The invention discloses a method for enhancing the performance of cement mortar through acidification electric field pre-carbonization. The method comprises the steps that the cement mortar comprises total amount standard sand, total amount cement, total amount mixing water and an acid reagent; the method comprises the following steps: mixing 10% of total cement, 80% of total mixing water and an acid reagent to obtain acidified cement paste, applying direct current to the acidified cement paste for 5-25 minutes, introducing CO2 into the acidified cement paste, continuously stirring, and completing pre-carbonization to obtain acidified pre-carbonized cement paste; and mixing the total amount of standard sand, the residual cement in the total amount of cement, the residual mixing water in the total amount of mixing water and the acidified pre-carbonized cement paste, and stirring for 3-5 minutes. According to the present invention, after the acid reagent is added to perform acidification treatment on the cement slurry, the CO2 is introduced into the cement slurry while the direct current is applied, such that the large amount of the greenhouse gas CO2 can be absorbed, the mechanical property of the concrete can be substantially improved, the CO2 source is wide, the cost is low, and the concrete production cost can be saved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of building materials, and particularly relates to a method for enhancing the performance of cement mortar by acidified electric field pre-carbonization. Background Art

[0002] The cement production industry emits approximately 1.35 billion tons of CO2 every year, accounting for 7% of the greenhouse gases released into the environment, imposing a heavy burden on environmental protection.

[0003] Although cement mortar products can re-absorb some of the carbon dioxide emitted during the production process through chemical reactions in the natural environment, this natural process is very slow and may take hundreds of years. Additionally, the carbonization process of absorbing carbon dioxide will cause corrosion of the steel bars in the cement mortar and reduce the mechanical properties of the cement mortar.

[0004] Therefore, a method that can absorb carbon dioxide while avoiding the reduction of the performance of cement mortar is needed. Summary of the Invention

[0005] The present invention provides a method for enhancing the performance of cement mortar by acidified electric field pre-carbonization to solve the above problems.

[0006] To achieve the above object, the technical solution of the present invention is as follows:

[0007] A method for enhancing the performance of cement mortar by acidified electric field pre-carbonization includes the following steps:

[0008] S1: The cement mortar includes total standard sand, total cement, total mixing water, and acid reagent;

[0009] Take 10% of the total cement, 80% of the total mixing water, and the acid reagent and mix them to obtain an acidified cement paste. Apply direct current to the acidified cement paste for 5 - 25 minutes, and at the same time, introduce CO2 into the acidified cement paste and continuously stir to complete pre-carbonization and obtain an acidified pre-carbonized cement paste;

[0010] S2: Mix the total standard sand, the remaining cement in the total cement, the remaining mixing water in the total mixing water, and the acidified pre-carbonized cement paste, and stir for 3 - 5 minutes.

[0011] Further, the acid reagent is acetic acid with a concentration of 99.5%.

[0012] Further, in the cement mortar, by weight, the total cement is 525 parts, the total standard sand is 1312.5 parts, the total mixing water is 257.5 parts, and the acid reagent is 5 parts.

[0013] Further, the voltage of the direct current is 30V.

[0014] Further, the purity of the introduced CO2 is 95%-99%, and the rate of introducing CO2 is 500 mL / min.

[0015] Further, in S1, the stirring method is to use a magnetic stirrer for stirring, and the rotational speed of the magnetic stirrer is 900 r / min.

[0016] Further, in S2, the stirring method is to use an automatic cement mortar mixer for stirring, and the rotational speed of the automatic cement mortar mixer is 1000-2000 rpm.

[0017] Further, the cement is ordinary Portland cement, and its strength grade is 42.5, 42.5R, 52.5 or 52.5R.

[0018] The beneficial effects of the present invention are as follows:

[0019] A method for enhancing the performance of acidified electric field pre-carbonized cement mortar disclosed in the present invention, after acidifying the cement paste by adding an acid reagent, and then introducing CO2 into the cement mortar while applying a direct current, can not only absorb a large amount of greenhouse gas CO2, but also greatly improve the mechanical properties of the cement mortar, and can also significantly improve the mechanical properties of the concrete prepared from the cement mortar prepared by using this method. Moreover, since the source of CO2 is extremely wide and the cost is low, while improving the mechanical properties of the cement mortar and concrete, the cost will also be saved. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for the description of the embodiments or the prior art. Obviously, the drawings in the following description are some embodiments of the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative efforts.

[0021] Figure 1 It is a schematic structural diagram of a device used for a method for enhancing the performance of acidified electric field pre-carbonized cement mortar disclosed in an embodiment of the present invention;

[0022] Figure 2 It is a flow chart of a method for enhancing the performance of acidified electric field pre-carbonized cement mortar disclosed in an embodiment of the present invention;

[0023] Figure 3 It is the 7-day compressive strength results of mortar specimens prepared by the methods of Examples 1-5 and Comparative Examples 1-7 of the present invention;

[0024] Figure 4The 28-day compressive strength results of the mortar specimens prepared by the methods of Examples 1-5 and Comparative Examples 1-7 of the present invention;

[0025] Figure 5 The 7-day flexural strength results of the mortar specimens prepared by the methods of Examples 1-5 and Comparative Examples 1-7 of the present invention;

[0026] Figure 6 The 28-day flexural strength results of the mortar specimens prepared by the methods of Examples 1-5 and Comparative Examples 1-7 of the present invention.

[0027] In the figure: 1. DC power supply; 2. Reinforcing bar at the negative pole of the power supply; 3. Carbon rod at the positive pole of the power supply; 4. Magnetic stirrer; 5. Air conditioner; 6. Carbon dioxide gas cylinder; 7. Beaker. Specific embodiments

[0028] To make the objectives, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings in the embodiments of the present invention. Apparently, the described embodiments are some, but not all, of the embodiments of the present invention. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without making creative efforts shall fall within the protection scope of the present invention.

[0029] The principle involved in the present application:

[0030] When preparing an acidified cement solution (slurry), acetic acid first undergoes an acid-base neutralization reaction with calcium hydroxide in the cement. The strongly alkaline reaction environment is not conducive to the rapid dissolution of active substances. After adding acetic acid (HAc), the strong alkaline environment around the cement particles can be reduced, thereby promoting the dissolution of active substances (such as tricalcium silicate and dicalcium silicate); at the same time, the carboxyl group (-COOH) in acetic acid can form a chelate with Ca 2+ to further accelerate the dissolution of active substances in the cement. Although the introduction of acetic acid will temporarily reduce the pH value of the solution, the continuous dissolution and release of active substances can increase the pH value of the hydration reaction and gradually reconstruct the strongly alkaline conditions conducive to the formation of calcium silicate hydrate (C-S-H gel), thereby eliminating the adverse effects brought by the addition of acetic acid. Therefore, adding an appropriate amount of acetic acid can accelerate the dissolution of active substances without affecting the strongly alkaline environment required for the formation of C-S-H gel. As a weak acid, acetic acid can slowly release H + , which enables it to continuously promote the progress of the hydration reaction without significantly reducing the alkalinity of the reaction environment, and also increases the content of C-S-H gel, significantly improving the mechanical properties of the cement mortar.

[0031] When an electric current and CO2 are applied to the acidified cement paste, acetic acid (HAc) first undergoes an acid-base neutralization reaction with calcium hydroxide in the cement to form calcium acetate and water. Since the solubility of calcium acetate is significantly higher than that of calcium hydroxide, this process promotes the release of more Ca 2+ into the solution. After applying the electric field, the solution temperature shows a linear upward trend (about 3°C / 5 min). This thermal effect increases the solubility of calcium hydroxide, thereby increasing the concentration of Ca 2+ in the solution. According to Le Chatelier's principle, the presence of acetic acid will promote the CO2 dissolution equilibrium to shift in the direction of forming carbonate ions, thus significantly increasing the concentration of CO3 2- in the solution; near the cathode, due to the continuous generation of OH - by water electrolysis, this also effectively promotes the dissolution of CO2. At this time, a large amount of CO3 2- and Ca 2+ are free in the solution and react with each other to form calcium carbonate particles at the nano or sub-micron scale. Under the drive of the electric field, the directional migration of charged particles significantly increases the formation rate of calcium carbonate, and part of the crystal form of calcium carbonate will gradually change into a prismatic shape. The generated prismatic calcium carbonate crystals have higher mechanical properties due to their more stable structure, and can enhance the overall strength of the cement mortar. The carboxyl functional groups in the system preferentially anchor calcium ions through coordination, which not only shortens the nucleation induction period of calcium carbonate, but also realizes crystal form selection through interface energy regulation - while inhibiting the growth of conventional calcite, it promotes the formation of mesocrystalline products such as metastable amorphous calcium carbonate (ACC) and vaterite. These non-equilibrium crystals with high specific surface area act as nano-fillers in the cement pores to increase the density and as heterogeneous nucleation sites to accelerate the hydration crystallization process of silicate minerals, ultimately forming a composite material system with multi-scale synergistic enhancement.

[0032] Adding CO2 to OPC-based concrete or mortar by the acidification-electricity pre-carbonation method will change the degree of hydration of C3A. The final reaction products are mainly determined by the molar ratios of CO2 / Al2O3 and C3A / SO3. For example, if the molar ratio of C3A / SO3 in the cement is close to 1, the hydration of CO2-modified C3A is as follows:

[0033]

[0034] If CO2 is continuously introduced, it will cause partial or complete replacement of semi-bicarbonate by mono-bicarbonate. According to the above equation, introducing CO2 into cement mortar will change the mineral properties of hydrated cement, promote the formation and stabilization of more ettringite, and increase the formation of mono-carbonate. These changes contribute to improving the strength and durability of cement mortar. The formation of ettringite will lead to the formation of more solid products, and its volume expansion property can reduce the porosity of cement mortar, thus enhancing its strength. In addition, the bulk modulus of mono-carbonate is significantly higher than that of other hydrated products, so increasing the formation of mono-carbonate may also improve the strength and hardness of cement mortar.

[0035] At the same time, a large amount of nano- and sub-micron CaCO3 is generated during the acidification-electricity pre-carbonation process. Before the nano- and sub-micron calcium carbonate reaches a certain content, the porosity will decrease with the prolongation of the action time, thus optimizing the pore structure. In addition, this process improves the morphology of CH crystals, refining them from hexagonal plate-like to prismatic shape. The generation of nano-calcium carbonate will also increase the content of CO3 2- in the solution. CO3 2- may replace SO4 2- in ettringite or prevent the transformation of ettringite, thus stabilizing its structure and further enhancing the density of cement mortar.

[0036] Moreover, acidification-electricity pre-carbonation also makes up for the disadvantages of the electricity pre-carbonation method and the pre-carbonation method to a certain extent. During the electricity pre-carbonation method and the pre-carbonation method, due to the excessive reaction degree, partial decalcification of C-S-H gel will generate CaCO3. Since the hardness and solid phase volume of CaCO3 are higher than those of C-S-H, the carbonation products of CaCO3 increase the strength of cement mortar in the early stage of the carbonation reaction. However, in the later stage of the pre-carbonation reaction, due to the consumption of C-S-H, the increase in its later strength is relatively small compared with the early strength. And due to the addition of acetic acid in acidification-electricity pre-carbonation, the content of C-S-H gel is increased, which not only significantly improves the early strength but also can significantly enhance the later strength.

[0037] Examples

[0038] Example 1:

[0039] A method for enhancing the performance of cement mortar by acidification-electric field pre-carbonation, step S1 (electricity pre-carbonation) is adopted as Figure 1Performed by the device shown, the device includes a DC power supply 1, a negative electrode steel bar 2 of the power supply, a positive electrode carbon rod 3 of the power supply, a magnetic stirrer 4, an air conditioner 5, a carbon dioxide gas cylinder 6, and a beaker 7. The positive electrode of the DC power supply is electrically connected to the positive electrode carbon rod 3 of the power supply, the negative electrode of the DC power supply 1 is electrically connected to the negative electrode steel bar 2 of the power supply. The ends of the positive electrode carbon rod 3 and the negative electrode steel bar 2 are immersed in the cement paste in the beaker. A magnetic stirrer is provided at the bottom of the beaker. CO2 in the carbon dioxide gas cylinder 6 is bubbled into the acidified cement paste in the beaker through the air conditioner 5 and a pipeline for electro - pre - carbonization.

[0040] A method for enhancing the performance of acidified electric - field pre - carbonized cement mortar, comprising the steps:

[0041] S1: Take 10% of the total amount of cement (52.5 parts by weight), 80% of the total amount of mixing water (206 parts by weight), and 5 parts by weight of acetic acid (concentration 99.5%) and add them into a beaker, mix to obtain an acidified cement paste. Apply 30V DC power for 5 minutes to the acidified cement paste. At the same time, use the air conditioner to directly bubble CO2 into the acidified cement paste at a gas flow rate of 500 mL / min for 5 minutes. The purity of CO2 is 95%. During this process, continuously stir through a magnetic stirrer. The rotation speed of the magnetic stirrer is 900 r / min. After the pre - carbonization is completed, an acidified pre - carbonized cement paste is obtained. In the cement mortar, by weight, the total amount of cement is 525 parts, the total amount of standard sand is 1312.5 parts, and the total amount of mixing water is 257.5 parts; the cement is 42.5 ordinary Portland cement.

[0042] S2: Add the total amount of standard sand, the remaining cement in the total amount of cement, the remaining mixing water in the total amount of mixing water, and the acidified pre - carbonized cement paste into an automatic cement mortar mixer. The rotation speed of the automatic cement mortar mixer is 2000 rpm, and the mixing time is 3 minutes.

[0043] The flow chart of this method is as Figure 2 shown.

[0044] Example 2:

[0045] The difference between this example and Example 1 is only that, in this example, the acidified cement paste is energized with direct current for 10 minutes, and at the same time, CO2 is introduced for 10 minutes.

[0046] Example 3:

[0047] The difference between this example and Example 1 is only that, in this example, the acidified cement paste is energized with direct current for 15 minutes, and at the same time, CO2 is introduced for 15 minutes.

[0048] Example 4:

[0049] The difference between this embodiment and Embodiment 1 is only that, in this embodiment, the acidified cement paste is energized with direct current for 20 min, and CO2 is introduced for 20 min at the same time.

[0050] Example 5:

[0051] The difference between this embodiment and Embodiment 1 is only that, in this embodiment, the acidified cement paste is energized with direct current for 25 min, and CO2 is introduced for 25 min at the same time.

[0052] Comparative Example

[0053] Comparative Example 1:

[0054] The difference between this comparative example and Embodiment 1 is only that, in this comparative example, in S1, acetic acid is not added, and the total amount of mixing water is 262.5 parts.

[0055] Comparative Example 2:

[0056] The difference between this comparative example and Embodiment 2 is only that, in this comparative example, in S1, acetic acid is not added, and the total amount of mixing water is 262.5 parts.

[0057] Comparative Example 3:

[0058] The difference between this comparative example and Embodiment 3 is only that, in this comparative example, in S1, acetic acid is not added, and the total amount of mixing water is 262.5 parts.

[0059] Comparative Example 4:

[0060] The difference between this comparative example and Embodiment 4 is only that, in this comparative example, in S1, acetic acid is not added, and the total amount of mixing water is 262.5 parts.

[0061] Comparative Example 5:

[0062] The difference between this comparative example and Embodiment 5 is only that, in this comparative example, in S1, acetic acid is not added, and the total amount of mixing water is 262.5 parts.

[0063] Comparative Example 6:

[0064] The difference between this comparative example and Embodiment 1 is only that, in this comparative example, in S1, acetic acid is not added, and the total amount of mixing water is 262.5 parts.

[0065] Comparative Example 7:

[0066] The difference between this comparative example and Embodiment 1 is only that, in this comparative example, in S1, CO2 is not introduced into the cement paste, direct current is not applied, and acetic acid is not added, and the total amount of mixing water is 262.5 parts.

[0067] The mix proportions of the cement mortar for Examples 1-5 and Comparative Examples 1-7, as well as the power-on and CO₂-passing times, are shown in Table 1 below:

[0068] Table 1 Mix Proportions, Acid Addition Amounts, Power-on and CO₂-passing Times of Cement Mortar for Examples 1-5 and Comparative Examples 1-7

[0069]

[0070] The compressive strength and flexural strength of the cement mortar after being stirred by the automatic cement mortar mixer for Examples 1-5 and Comparative Examples 1-7 were tested:

[0071] (1) Compressive strength test method:

[0072] The cement mortar after being stirred by the automatic cement mortar mixer was secondarily vibrated and placed into a triple cube mold with a side length of 70.7 mm. Six test blocks were prepared for each example and each comparative example. The average compressive strength and average flexural strength of the cement mortar were tested after 7-day and 28-day water bath curing, and the test was carried out with reference to the Standard for Test Methods of Basic Properties of Building Mortar JGJ / T 70-2009;

[0073] (2) The results are shown in Table 2 and Figures 3 - 6

[0074] Table 2 7-day Compressive Strength Results of Examples 1-5 and Comparative Examples 1-7

[0075]

[0076] According to Table 2 and Figure 3Data shows that, compared with the untreated control group (Comparative Example 7), the compressive strengths of the mortar specimens prepared by acidification - electro - carbonation pretreatment for 5, 10, 15, 20 min increased by 31.36%, 38.26%, 51.73%, 59.35% respectively. Although there was a slight decrease in the 25 - min group, the strength gain still remained at 49.73%, indicating that the acidification - electro - carbonation method can significantly improve the compressive strength of cement mortar. Compared with the mortar specimens prepared by only adding acetic acid without electro - carbonation treatment (Comparative Example 6), the improvement amplitudes of the compressive strengths of the mortar specimens prepared by the acidification - electro - carbonation method for 5, 10, 15, 20, 25 min were 8.51%, 14.20%, 25.33%, 31.63%, 23.68% respectively, further verifying the strengthening and promoting effect of the electrochemical action on the acidification effect. In addition, under the same electro - carbonation and CO₂ treatment conditions, the compressive strengths of the mortar specimens prepared by the acidification - electro - carbonation method for 5, 10, 15, 20, 25 min (Examples 1 - 5) were increased by 19.30%, 15.39%, 27.32%, 23.92%, 30.98% respectively compared with the electro - carbonation method (Comparative Examples 1 - 5), indicating that the acidification - electro - carbonation method can further improve the compressive strength of cement mortar on the basis of the electro - carbonation method.

[0077] Figure 4 Figure shows the 28 - day compressive strength results of the mortar specimens prepared in Examples 1 - 5 and Comparative Examples 1 - 7. It can be seen from the figure that after 28 - day curing, the compressive strength of the mortar specimens prepared by this method is still higher than that of the concrete specimens prepared by the non - acidified electro - carbonation method;

[0078] The results of the 7 - day flexural strength of the mortar specimens prepared in Examples 1 - 5 and Comparative Examples 1 - 7 are as Figure 5 shown. It can be seen from the figure that the 7 - day flexural strength of the mortar specimens prepared by this method - acidification - electro - carbonation method is significantly higher than that of the mortar specimens prepared by the electro - carbonation method, proving that the combination of acidification treatment and electro - carbonation method can improve the flexural strength of mortar specimens;

[0079] The results of the 28 - day flexural strength of the mortar specimens prepared in Examples 1 - 5 and Comparative Examples 1 - 7 are as Figure 6 shown. It can be seen from the figure that the 28 - day flexural strength of the mortar specimens prepared by this method - acidification - electro - carbonation method is still higher than that of the mortar specimens prepared by the electro - carbonation method.

[0080] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those of ordinary skill in the art should understand that they can still modify the technical solutions described in the foregoing embodiments, or perform equivalent replacements for some or all of the technical features; and these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for enhancing the performance of acidified electric field pre-carbonized cement mortar, characterized in that It includes the following steps: S1: The cement mortar includes total standard sand, total cement, total mixing water, and acid reagent; Take 10% of the total cement, 80% of the total mixing water, and the acid reagent and mix them to obtain an acidified cement paste. Apply direct current to the acidified cement paste for 5 - 25 minutes, and at the same time, introduce CO2 into the acidified cement paste and continuously stir to complete pre-carbonization to obtain an acidified pre-carbonized cement paste; S2: Mix the total standard sand, the remaining cement in the total cement, the remaining mixing water in the total mixing water, and the acidified pre-carbonized cement paste, and stir for 3 - 5 minutes.

2. The method for enhancing the performance of acidified electric field pre-carbonized cement mortar according to claim 1, wherein, The acid reagent is acetic acid, and its concentration is 99.5%.

3. The method for enhancing the performance of acidified electric field pre-carbonized cement mortar according to claim 1, characterized in that In the cement mortar, by weight, the total cement is 525 parts, the total standard sand is 1312.5 parts, the total mixing water is 257.5 parts, and the acid reagent is 5 parts.

4. The method for enhancing the performance of acidified electric field pre-carbonized cement mortar according to claim 1, wherein, The voltage of the direct current is 30V.

5. The method for enhancing the properties of acidified electric field pre-carbonized cement mortar according to claim 1, characterized in that, The purity of the introduced CO2 is 95% - 99%, and the speed of introducing CO2 is 500 mL / min.

6. The method for enhancing the performance of acidified electric field pre-carbonized cement mortar according to claim 1, characterized in that In S1, the stirring method is to use a magnetic stirrer for stirring, and the rotation speed of the magnetic stirrer is 900 r / min.

7. The method for enhancing the performance of acidified electric field pre-carbonized cement mortar according to claim 1, characterized in that In S2, the stirring method is to use an automatic cement mortar mixer for stirring, and the rotation speed of the automatic cement mortar mixer is 1000 - 2000 rpm.

8. The method for enhancing the performance of acidified electric field pre-carbonized cement mortar according to claim 1, characterized in that, The cement is ordinary Portland cement, and its strength grade is 42.5, 42.5R, 52.5, or 52.5R.

Citation Information

Patent Citations

  • Cement-based self-leveling mortar

    CN102432255A

  • Cement-based waterproof material and preparation method thereof

    CN104230264A

  • Method for recycling waste mortar by using citric acid and alkaline accelerator

    CN112707699A

  • Method for enhancing compressive strength of cement mortar by electrifying pre-carbonization method

    CN118955171A

  • System and method for accelerating carbonization or mineralization of cement base material by electrifying

    CN119533749A